Experimental Research on Surge Characteristics of Centrifugal Compressors - Yuanyang, Zhao; Qichao, Yang; Liansheng, Li; Guangbin, Liu; Yue, Shu (Journal of Vibration Testing and System Dynamics, 2026)
Centrifugal compressors are widely used in many process industries. The stability is one of the most important characteristics of centrifugal compressor. When the compressor operates under the condition of small mass flow rate, the working conditions of rotating stall and surge will occur. The surge of the centrifugal compressor is researched by experiment. The signals are tested and analyzed when surge condition occurs in this paper. The suction and discharge pressures are tested under the surge working conditions. The pulsation frequency of the pressures is very small (6Hz), and it is about 0.03 of the rotating speed frequency. The vibration of the inlet pipes is researched as a parameter of the surge of compressor. The vibration test results show that it can be as an important signal to estimate the surge working condition. When the surge occurs, the pipe vibration amplitude at the low frequency is bigger, and it is about four times of that at the working frequency. However, the maximum amplitude of pipe vibration is not change with rotation speeds.